EFL Students’ Perceptions and Preferences of The Video Use as a Replacement for Traditional Lecture Method - Anisa Anisa (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This study aimed to investigate students’ perceptions and preferences of video use as a replacement for traditional lecture during e-learning in times of the COVID-19 pandemic. This study used two-staged mixed-method. The design of this study was sequential explanatory. This study used 30 closed-ended questionnaires and focus group discussions as the instrument to gain a rich understanding of students’ video experiences, perceptions and preferences. Data were collected from 108 EFL students through an online questionnaire using Google form and face-to-face focus group discussion. Results show that (1) Most of students showed positive perceptions of the use of video as a replacement for traditional lecture during e-learning in times of the COVID-19 Pandemic. It can be seen from the questionnaire results that 83.3% of students showed positive perception. (2) Students mostly preferred video-based learning if there is post-videos watching activities such as reviewing, re-explaining, question and answer, etc. Furthermore, the types of videos they preferred are instructor-created videos and animation videos from YouTube